MEDICINAL PLANTS AND THEIR USE - Fayziyev Xayrullaxon Omonilloyevich; Asqarov Ibrohimjon Rahmonovich; Islomov Akmal Xushvaqovich; Atqiyayeva Sanobarxon Ismoilxon qizi; Xabibullayev Abdullazizxon Omonillo o‘g‘li (Web of Journals Publishing, 2024)
This article provides information on medicinal plants found in nature and the history of their use, unique types of medicinal properties and methods of use, as well as the results of the impact of the human factor on them.
Keywords: Medicinal plant, alkaloid, glycoside, essential oil, vitamin, starch, phytoncide.